An insight into human rights in the engineering workplace and education. Issue 39 (2022) - Bula, Ines; Kent, Mary Doyle; Retkoceri, Blertë; O'Neill, Brenda; Stapleton, Larry; Bula, Edin; Hajrizi, Edmond
Abstract: The paper focuses on three aspects. The first focus of this research is to investigate the challenges of women working as engineers in Kosovo and Ireland. The second focus is to investigate the challenges of both men and women working as engineers in Kosovo and Ireland. The third focus is to investigate the awareness of applicable laws regarding human rights and/or gender equality and the possibility of the inclusion of human rights and/or gender equality laws within education to help deal with discrimination problems that may arise in the future. A comparison is made between similar groups in Kosovo and Ireland. The survey asks questions about the perceived socio-economic difficulties, flexibility issues and lack of opportunity for career advancement for women and men working as engineers. In addition the survey reviews the possibility of the inclusion of human rights and/or gender equality laws during education to help deal with discrimination problems that may arise in the future.